Making It Active: A Cohort Study of a Large-Group Learning Session to Improve Nutrition-Related Knowledge and Skills for Second-Year Medical Students - Gregory W. Schneider; Julia Bisschops; Prasad Bhoite; Sabyasachi Moulik (Journal of Medical Education and Curricular Development)
Introduction Despite the well-established role of nutrition in preventing and managing chronic diseases, medical education often lacks sufficient training in nutrition counseling. To address this gap, the Florida International University Herbert Wertheim College of Medicine introduced a 2-hour, case-based active learning session on diabetes-related nutrition education. This cohort study evaluates the session's effectiveness in improving students’ knowledge of nutritional therapy for diabetes, evidence-based research methods, and the role of social determinants of health (SDOH). Methods The study followed two cohorts of second-year medical students from the Classes of 2024 and 2025. Students participated in a session that combined an introductory lecture with two small-group case-based exercises. Interactive technology-enhanced quizzes assessed pre- and post-session knowledge on diabetes nutrition, research methodology, and SDOH considerations. Additionally, end-of-course surveys evaluated students’ perceptions of learning. Statistical analyses included the Two-Proportion Z-Test for quiz results and the Mann–Whitney U Test for survey responses. Results Significant improvements were observed in students’ knowledge of nutritional management for diabetes and evidence-based research strategies ( p  < 0.05). However, no significant changes were found in SDOH-related knowledge, likely due to high pre-session baseline scores. End-of-course surveys indicated positive student perceptions of the session, with scores largely stable across cohorts, though perceptions of nutritional guidance benefits were slightly lower in the Class of 2025 ( p  = 0.0282). Discussion The case-based active learning session effectively enhanced knowledge acquisition and was well-received by students while requiring minimal faculty involvement. Future research should assess long-term retention and integrate nutrition education longitudinally across the curriculum.